Antecedents of Norwegian Adolescents’ Choice of Educational Pathway in Hospitality and Tourism - Dagsland, Åse Helene Bakkevig; Mykletun, Reidar J.; Einarsen, Ståle Valvatne (Nordic Journal of Working Life Studies, 2017)
This study investigates the extent to which Norwegian adolescents (age 15–16 years) choose vocational foundation classes for high school related to the hospitality industry and intend to complete their certificate of apprenticeship in this field. Departing from the concepts of beliefs, behavioral intentions, and background factors, the study explores pupils’ beliefs about work in the hospitality industry and the ways in which beliefs and social and informational background factors predict their choices. Data were collected in 2002 (n = 1863) and 2011 (n = 1839) using questionnaires, allowing to explore differences between the two measurements. The results showed a decrease in the number of pupils choosing these vocational courses between 2002 and 2011. Yet, pupils’ beliefs about work in the industry were positive, with no major change between the two measures. These beliefs and their own experiences from encounters with the industry emerged as the most significant predictors of the pupils’ choices.